Varieties Of Chemical Additives for Concrete Mixtures of The Method for Producing Their Mechanisms of Action Their Mechanisms of Action they’re On Cons Concrete Mixes and Concrete - Teshaboeva Nodira Djuraevna (Zien Journals, 2021)
The article describes a method for determining various chemical additives are widely used in modern concrete technology. They allow us to direct the formation of the cement composition and improve concrete technologies at all stages of the production of concrete and reinforced concrete products and structures. Chemical additives are obtained from additional products or are specially designed synthesized substances.
Keywords: concrete; modifier; tests; hot